A Determination of PV and Wind Power Plant Penetration into a Power System: a Case of Java Bali - Musthafa Abdur Rosyied; Sarjiya Sarjiya; Lesnanto Multa Putranto; Izzuddin Fathin Azhar; Eko Yudo Pramono (Forum Pendidikan Tinggi Teknik Elektro Indonesia (FORTEI), 2020)
PT. PLN (Persero) has planned to develop a new renewable energy which has a minimum energy mix of 23% in 2025 and 31% in 2030. An intermittent renewable energy plant, which is uncontrollable and unpredictable, will begin to be massively used. Associated to the intermittent nature of the of intermittent renewable energy source (IRES), adequate system flexibility is necessary. This study determined the penetration level IRES generating unit using the systems load and existing generating unit ramping rate characteristic, IRES generating unit’s ramping rate and system’s technical minimum load (TML) on the Java Bali System based on the 2017 operation condition. The results showed that the TML value of the operating plant was 12164,69 MW. The ramping up and down capabilities of conventional power plants are 945.04 MW / 30 min and 4006.08 MW / 30 min where ± 5% of penetration of IRES was still applicable for the Java Bali System.